Central line‐associated bloodstream infection in childhood malignancy: Single‐center experience. Issue 7 (26th July 2017) - Miliaraki, Marianna; Katzilakis, Nikolaos; Chranioti, Ioanna; Stratigaki, Maria; Koutsaki, Maria; Psarrou, Maria; Athanasopoulos, Emmanouil; Stiakaki, Eftichia
Abstract: Background: Central line‐associated bloodstream infection (CLABSI) is a common complication in children with malignancy, often leading to prolonged hospitalization, delay in chemotherapy or catheter removal. This retrospective epidemiological study reviewed 91 children with malignancy over a 5 year period between 2011 and 2015 and analyzed potential risk factors for CLABSI. Methods: Symptoms, laboratory and microbiology characteristics, subsequent treatment and outcome were recorded and analyzed. All the collected data were processed through SPSS for statistical analysis. Results: Among 40 episodes of CLABSI recorded in 30 patients, the rate of CLABSI was estimated as 2.62 episodes per 1, 000 days of central venous catheter (CVC) carriage. Most of the bacterial pathogens isolated in CLABSI episodes were Gram positive, including different strains of staphylococci, while Gram‐negative bacteria were involved in 30% of episodes. Invasive mycosis was isolated in 7.5% of episodes, accounting for the highest catheter removal rate. Intensive chemotherapy and prolonged hospitalization proved to be independent risk factors for CVC infection. In children with neutropenia, the risk for CLABSI was also fourfold greater ( P  =   0.001). Children with leukemia had a fivefold greater risk for CLABSI ( P  =   0.005). Finally, although 36% of patients received antibiotic lock therapy, in 15% of these patients catheter replacement could not be avoided due to persistent serious infection. Conclusions: Younger age, neutropenia, hematologic malignancy and longer catheterization are important risk factors for CLABSI, but further research is required for the prevention of catheter‐related infection in children with malignancy.